2008
DOI: 10.1002/app.28546
|View full text |Cite
|
Sign up to set email alerts
|

Properties of high‐impact polystyrene/organoclay nanocomposites synthesized via in situ polymerization

Abstract: High-impact polystyrene (HIPS)/organically modified montmorillonite (organoclay) nanocomposites were synthesized via in situ polymerization. The effects of the organoclay on the morphology and material properties of HIPS/organoclay nanocomposites were investigated. Xray diffraction and transmission electron microscopy experiments revealed that intercalation of polymer chains into silicate layers was achieved, and the addition of nanoclay led to an increase in the size of the rubber domain in the composites. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The effect of the clay in enhancing thermal stability can be explained by the silicate layers with a high aspect ratio, which could hinder the diffusion of volatile degradation matter out of the polymer matrix. 18,30,34 From the results included in Figure 5a, it is clear that the temperature where the material is degraded by 10% (T 10% ) increases by as much as 25 1C with the addition of 2 wt% C30B, whereas a further increase in the C30B clay loading to 5 wt% does not improve the thermal stability of the nanocomposite material significantly. The differential thermogravimetric analysis (DTGA) curves showed a double peak when the HIPS material was undergoing degradation, indicating that there was a degradation mechanism taking place in two separate steps.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…The effect of the clay in enhancing thermal stability can be explained by the silicate layers with a high aspect ratio, which could hinder the diffusion of volatile degradation matter out of the polymer matrix. 18,30,34 From the results included in Figure 5a, it is clear that the temperature where the material is degraded by 10% (T 10% ) increases by as much as 25 1C with the addition of 2 wt% C30B, whereas a further increase in the C30B clay loading to 5 wt% does not improve the thermal stability of the nanocomposite material significantly. The differential thermogravimetric analysis (DTGA) curves showed a double peak when the HIPS material was undergoing degradation, indicating that there was a degradation mechanism taking place in two separate steps.…”
Section: Resultsmentioning
confidence: 91%
“…Other studies 5,14,30,31 have shown that the elongation at break is greatly decreased upon addition of clay. It can therefore be postulated that the decrease in the impact strength is a result of the organoclay degradation during melt processing, in which the collapsed organoclay structures cause a buildup of stress in the system.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Polymers exhibit inferior impact resistance, stiffness, and strength to weight ratio, compared to fibrous composites that are reinforced with fibers or yarns, which play a key role in introducing high impact resistance, and superior mechanical properties into the composite materials. Numerous attempts have been made to enhance both impact resistance and mechanical properties of polymer materials by blending two or more materials [8][9][10]. Polymethyl methacrylate (PMMA) and polycarbonate (PC) are often utilized for impact resistant polymer materials because they have good impact resistance as well as relatively good mechanical properties such as Young's modulus or tensile strength.…”
Section: Introductionmentioning
confidence: 99%